Unraveling the Guardians of Growth: A Comprehensive Analysis of the Aux/IAA and ARF Gene Families in Populus simonii - Kewei Cai; Qiushuang Zhao; Jinwang Zhang; Hongtao Yuan; Hanxi Li; Lu Han; Xuebo Li; Kailong Li; Tingbo Jiang; Xiyang Zhao (Plants, 2023)
The auxin/indole-3-acetic acid (Aux/IAA) and auxin response factor (ARF) genes are two crucial gene families in the plant auxin signaling pathway. Nonetheless, there is limited knowledge regarding the Aux/IAA and ARF gene families in Populus simonii. In this study, we first identified 33 putative PsIAAs and 35 PsARFs in the Populus simonii genome. Analysis of chromosomal location showed that the PsIAAs and PsARFs were distributed unevenly across 17 chromosomes, with the greatest abundance observed on chromosomes 2. Furthermore, based on the homology of PsIAAs and PsARFs, two phylogenetic trees were constructed, classifying 33 PsIAAs and 35 PsARFs into three subgroups each. Five pairs of PsIAA genes were identified as the outcome of tandem duplication, but no tandem repeat gene pairs were found in the PsARF family. The expression profiling of PsIAAs and PsARFs revealed that several genes exhibited upregulation in different tissues and under various stress conditions, indicating their potential key roles in plant development and stress responses. The variance in expression patterns of specific PsIAAs and PsARFs was corroborated through RT-qPCR analysis. Most importantly, we instituted that the PsIAA7 gene, functioning as a central hub, exhibits interactions with numerous Aux/IAA and ARF proteins. Furthermore, subcellular localization findings indicate that PsIAA7 functions as a protein localized within the nucleus. To conclude, the in-depth analysis provided in this study will contribute significantly to advancing our knowledge of the roles played by PsIAA and PsARF families in both the development of P. simonii tissue and its responses to stress. The insights gained will serve as a valuable asset for further inquiries into the biological functions of these gene families.